(untitled) (Journal of Applied Oral Science, 2004)
This in vitro study evaluated and compared the efficacy of conventional (Kodak F-speed (Insight), Kodak) and a digital (DRS Gnatus System, Gnatus) radiographic imaging for diagnosis of simulated external root resorption cavities. Human mandibles containing teeth were covered with bovine muscle slices in order to simulate the soft tissues. Nine teeth out of each group of teeth were investigated. Initially, three periapical radiographs of each tooth were taken using a tube shift technique with mesial and distal angulations in both methods. All teeth were subsequently extracted and had 0.7 and 1.0-mm deep cavities prepared on their buccal, mesial and distal surfaces at the cervical, middle and apical thirds. Steel cylinder burs (DORMER® - HSS) with 0.7 and 1.0-mm diameter were used. Each tooth was replaced on its socket and new radiographs were taken. Three examiners, an endodontist (1), a radiologist (2) and a general dentist (3), evaluated the images. Results were compared by z-test and showed a higher number of cavities detected by the digital method compared to the conventional, regardless of the deepness of the cavity. In decreasing order, examiners 2, 3 and 1 exhibited different potentials of detection of cavities with the conventional method. Examiners 1 and 3 exhibited superior potential than examiner 2 for detection of cavities of different sizes with the digital method.